THE INFLUENCE OF DIGITAL LITERACY, PARENTAL AND PEER SUPPORT ON CRITICAL THINKING SKILLS IN THE AI ERA - Astuti, Dwi Puji; Kardiyem , Kardiyem; Setiyani , Rediana; Jaenudin, Ahmad (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
Critical thinking skills are essential and must be  in today's fast-paced and globalized worldconsidered. Critical thinking is necessary to evaluate information, solve problems, and make informed decisions in academic and real-world scenarios. The evolution of Artificial Intelligence (AI) technology has added a new dimension to educational technology. AI has the potential to revolutionize the world of education by personalizing learning experiences and providing real-time assessments, among other benefits. The integration of AI in the learning process is still debated regarding its pros and cons in supporting critical thinking. This research tries to examine critical thinking competencies in the AI era for students from various fields of study. The purpose of this study is to determine the positive and significant relationship between digital literacy, the role of parents, and the role of peers on students' critical thinking skills in the AI era. This study is a quantitative research with a correlational design. The sample used was 302 students of various study programs who were randomly selected from universities throughout Central Java. The data collection method used in this study is a survey using a questionnaire. The data analysis tool uses spss 26. The results of the study show that digital literacy and the role of parents have a positive and significant influence on critical thinking skills in the AI era. Peers have no effect on critical thinking skills in the AI era